DAMPAK PERUBAHAN IKLIM DAN STRATEGI ADAPTASI TANAMAN BUAH DAN SAYURAN DI DAERAH TROPIS / CLIMATE CHANGE IMPACT AND ADAPTATION SRATEGY FOR VEGETABLE AND FRUIT CROPS IN THE TROPIC REGION - Sarvina, Yeli (Badan Penelitian dan Pengembangan Pertanian, 2019)
Climate change has significant negative impact on agriculture in tropical region. Inrecent years, research on climate change has focused mainly on food crops while horticultural crops have received little attention. This paper is an overview of Indonesian future climate projection for precipitation, temperature and extreme climate, climate change impact and adaptation strategies on vegetable and fruit crops and future challenge for horticultural development under climate change. The climate change will decrease crop productivity and quality, increase the incidence of new pest and disease, and the outbreaks on vegetable and fruit crops. Further climate change will disrupt water availability, alter climate-crop suitability and cause crop failure due to extreme climate. Several adaptation measures have been developed in farming system, among other adjustment of planting time, using resistant varieties to environmental strees, adopting irrigation technology for efficient water use, using green house and increasing farmers and extention service capacity through climate field school. For future research it is necessary to assess climate projections with several scenarios and Global Circular Models (GCMs) and their impact on future vegetable and fruits crops by developing crop modeling which should be given a priority of in agriculture. This information crucially needed for adaptation strategy and a long term agricultural planning in the future.Keywords: Vegetable, fruit, climate change, global circular model, adaptation AbstrakPerubahan iklim berdampak negatif terhadap pertanian di daerah tropis. Selama ini penelitian dampak perubahan iklim terhadap pertanian lebih banyak dilakukan pada tanaman pangan, sementara pada tanaman hortikultura, khususnya sayuran dan buah-buahan masih terbatas. Tulisan ini merupakan tinjauan tentang proyeksi dampak perubahan iklim di Indonesia yang meliputi curah hujan, suhu udara, dan iklim ekstrim terhadap produksi tanaman buah dan sayuran, di samping berbagai upaya adaptasi yang telah dilakukan dan tantangan pembangunan hortikultura ke depan. Perubahan iklim pada tanaman sayuran dan buah-buahan terbukti menurunkan kuantitas dan kualitas produksi, munculnya hama penyakit baru, meningkatnya serangan hama dan penyakit, gagal panen, penurunan kapasitas air irigasi, perubahan kesesuian lahan dan tanaman. Beberapa langkah adaptasi yang sudah dilakukan yaitu penyesuaian sistem usaha tani yang meliputi penggunaan varietas toleran cekaman lingkungan, penyesuian waktu tanam, penggunaan teknik irigasi hemat air, pengembangan teknologi pencarian sumber daya air baru, penggunaan rumah kasa/rumah plastik, peningkatan kemampuan petani dan penyuluh dalam memahami perubahan iklim melalui sekolah lapang. Ke depan masih perlu dilakukan kajian proyeksi iklim dengan berbagai skenario dan berbagai Global circular model (GCM) serta kajian dampak perubahan iklim terhadap tanaman sayur dan buah unggulan melalui pengembangan pemodelan sistem usaha tani. Informasi proyeksi dampak perubahan iklim diperlukan sebagai upaya adaptasi dan perencanaan pembangunan pertanian yang dikaitkan dengan perubahan iklim.Kata kunci: Buah-buahan, sayuran, perubahan iklim, global circular model, adaptasi